Les milles visages de l’expertise. Savoir expert, savoir profane dans les procès pour infanticide à Florence au début du XXe siècle - Silvia Chiletti (Criminocorpus)
This article deals with the emergence of psychiatric issues in Italian criminal courts between 1900 and 1922, focusing on the specific case of infanticide from the sources of the State Archive of Florence. It analyzes how legal evidence about the mental state of the defendants is produced, by considering the role of medical experts, the legal frame that regulates testimonies about criminal responsibility, and the capacity of judges and attorneys to dispose of psychiatric knowledge according to precise judicial strategies. The article thus tries to delineate the peculiarities of this kind of medical and legal evidence, which is related not only to the specific crime of infanticide, but also to the transformations of Italian legal procedure during these years.